Innovation & Intellectual Property (UCT Press, 2024)
In the global knowledge economy, intellectual property (IP) rights – and the innovations they are meant to spur – are important determinants of progress. But what does this mean for the nations of Africa? One view is that strong IP protection can facilitate innovation in African settings. Others say that existing IP systems are simply not suited to the realities of African innovators. This book, based on case studies and evidence collected through research across nine countries in Africa, sheds new light on the complex relationships between innovation and intellectual property. It covers findings from Egypt, Nigeria, Ghana, Ethiopia, Uganda, Kenya, Mozambique, Botswana and South Africa, across many sites of innovation and creativity including music, leather goods, textiles, cocoa, coffee, auto parts, traditional medicine, book publishing, biofuels and university research. Various forms of intellectual property protection are explored: copyrights, patents, trademarks, geographical indications and trade secrets, as well as traditional and informal mechanisms of knowledge governance. The picture emerging from the empirical research presented in this volume is one in which innovators in diverse African settings share a common appreciation for collaboration and openness. And thus, when African innovators seek to collaborate, they are likely to be best served by IP approaches that balance protection of creative, innovative ideas with information-sharing and open access to knowledge. The authors, who come from a range of disciplines, are all experts in their fields, working together through the Open African Innovation Research and Training (Open A.I.R.) network (www.openair.org.za).